1987
DOI: 10.1128/mcb.7.4.1572
|View full text |Cite
|
Sign up to set email alerts
|

Unequal distribution of N6-methyladenosine in influenza virus mRNAs.

Abstract: Influenza virus mRNA is posttranscriptionally methylated at internal adenosine residues to form N6-methyladenosine (m6A). It has been previously shown that there is an average of three m6A residues per influenza virus mRNA (R. M. Krug, M. A. Morgan, and A. J. Shatkin, J. Virol. 20:45-53, 1976). To determine the distribution of m6A in the different influenza virus mRNAs, we purffied six of the mRNAs by hybrid selection, digested them with nuclease, and determined their methylation patterns by high-pressure liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 6 publications
0
50
0
Order By: Relevance
“…Therefore, methylation at this site is nonstpichiometric. Furthermore, the methyl addition found.in both the 13-and 39-base oligonucleotides is nonstoichiom.etric and corresponds to that reported for bPRL mRNA (22) and viral RNAs (18,21). One of the alternatives which may give rise to this nonstoichiometry is that the methyltransferase is influenced by the sequence context in which the consensus motif is located.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, methylation at this site is nonstpichiometric. Furthermore, the methyl addition found.in both the 13-and 39-base oligonucleotides is nonstoichiom.etric and corresponds to that reported for bPRL mRNA (22) and viral RNAs (18,21). One of the alternatives which may give rise to this nonstoichiometry is that the methyltransferase is influenced by the sequence context in which the consensus motif is located.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, as this region of RNA will be lost during processing, m6A at specific locations in precursor RNA is not conserved during maturation. Previous investigators exam- (9), and influenza virus mRNAs (21). The detailed kinetic studies of m6A in adenovirus nuclear and cytoplasmic RNAs demonstrated m6A conservation during mRNA formation (9,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we now know that many cellular mRNAs, including mRNAs encoding housekeeping genes, lack any m 6 A residues, while highly regulated mRNAs may contain 10 or more (2,3). The first demonstration of m 6 A residues on viral mRNAs soon followed and, using the biochemical approaches available at that time, a range of mRNAs encoded by several nuclear DNA and RNA viruses were then shown to bear fairly high levels of m 6 A, with the eight influenza A virus (IAV) mRNAs bearing an average of three m 6 A residues each (4)(5)(6)(7)(8)(9). Subsequent work looking at each individual IAV mRNA revealed that IAV mRNAs actually contain from 1 to 8 m 6 A residues each (Table 1) (5).…”
mentioning
confidence: 99%
“…Of these, by far the most prevalent internal modified base found on mRNAs is m 6 A, and recent work has now begun to reveal how m 6 A affects mRNA function and how to precisely map the m 6 A residues present on mRNAs (1)(2)(3). m 6 A is also highly prevalent on a wide range of different viral RNA species (4)(5)(6)(7)(8)(9)(10)(11)(12)(13), and recently, the first reports demonstrating a significant phenotypic effect of these m 6 A modifications have been published (10)(11)(12)(13)(14). Therefore, we will focus this review entirely on m 6 A and how this particular modification might affect different aspects of the viral life cycle.…”
mentioning
confidence: 99%